The influence of ACE inhibitors and ARBs on hospital length of stay and survival in people with COVID-19. (December 2020) - Braude, Philip; Carter, Ben; Short, Roxanna; Vilches-Moraga, Arturo; Verduri, Alessia; Pearce, Lyndsay; Price, Angeline; Quinn, Terence J.; Stechman, Michael; Collins, Jemima; Bruce, Eilidh; Einarsson, Alice; et al.
Highlights: Mortality from COVID-19 is not affected by prescription of ACEi and/or ARBs. Hospital stay is reduced in patients prescribed ACEi /. ARBs when diagnosed with COVID-19. This study reassures that continuation of ACEi / ARBs is not harmful, and may confer benefit in COVID-19. Abstract: Objective: During the COVID-19 pandemic the continuation or cessation of angiotensin-converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARBs) has been contentious. Mechanisms have been proposed for both beneficial and detrimental effects. Recent studies have focused on mortality with no literature having examined length of hospital stay. The aim of this study was to determine the influence of ACEi and ARBs on COVID-19 mortality and length of hospital stay. Methods: COPE (COVID-19 in Older People) is a multicenter observational study including adults of all ages admitted with either laboratory or clinically confirmed COVID-19. Routinely generated hospital data were collected. Primary outcome: mortality; secondary outcomes: Day-7 mortality and length of hospital stay. A mixed-effects multivariable Cox's proportional baseline hazards model and logistic equivalent were used. Results: 1371 patients were included from eleven centres between 27th February to 25th April 2020. Median age was 74 years [IQR 61–83]. 28.6% of patients were taking an ACEi or ARB. There was no effect of ACEi or ARB on inpatient mortality (aHR = 0.85, 95%CI 0.65–1.11). For those prescribed an ACEi or ARB, hospital stay was significantly reduced (aHR = 1.25, 95%CI 1.02–1.54, p = 0.03) and in those with hypertension the effect was stronger (aHR = 1.39, 95%CI 1.09–1.77, p = 0.007). Conclusions: Patients and clinicians can be reassured that prescription of an ACEi or ARB at the time of COVID-19 diagnosis is not harmful. The benefit of prescription of an ACEi or ARB in reducing hospital stay is a new finding.